Analisis Penerapan Rekayasa Nilai Pada Proyek Pembangunan Gedung Laboratorium Terpadu Kemaritiman - Sadik Ramdan Katili; Arfan Usman Sumaga; Apriyanto Pahrun (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study focuses on the analysis of the architectural section of the Maritime Integrated Laboratory Building Development Project, which constitutes a significant portion of the overall project cost. However, this section still has the potential for cost optimization through re-efficiency efforts. Therefore, the application of the Value Engineering (VE) method is necessary to identify and eliminate unnecessary costs and efforts, ultimately reducing the total value or cost of the project while maintaining its function and quality. The data required for this study include the Cost Budget Plan (Rencana Anggaran Biaya/RAB) and Unit Price Analysis (Analisa Harga Satuan Pekerjaan/AHSP). The research method consists of several stages: cost model analysis, breakdown of work items, Pareto analysis to identify high-cost contributors, creative development of design alternatives, and analytical decision-making using Life Cycle Cost (LCC) and the Analytical Hierarchy Process (AHP). Based on the VE analysis, it was found that the most significant cost-saving opportunities were in the wall and floor work components. After replacing the initial designs with the recommended alternatives, the total savings in construction costs reached Rp. 654,697,776.22 from the total architectural cost of Rp. 8,407,006,703.01, resulting in a savings percentage of 7.79%. Additionally, savings from the life cycle cost analysis amounted to Rp. 1,039,066,566.57. These results demonstrate that the Value Engineering approach is effective in achieving cost efficiency without compromising the functional integrity of the project.